Criminal Responsibility Against STM May 2 Bandar Lampung Students Who Conducted Brawls Carrying Sickle Sharp Weapons in the BLK Vocational School Environment, Bandar Lampung City (Decision Study Number: 30/Pid.Sus-Anak/2022/Pn.Tjk) - Lukmanul Hakim; Risti Dwi Ramasari; Massriyati Massriyati (CV. Rayyan Dwi Bharata, 2023)
Factors that cause children to fight with sickles in the SMK BLK school environment in Bandar Lampung City based on Decision Number: 30/Pid.Sus-Anak/2022/Pn Tjk are individual psychological factors themselves can cause crimes such as emotional power, low mentality, illness heart with victims, revenge. The factor of public ignorance is also a cause of criminal acts. This lack of outreach/education to the community is what causes this crime to occur in people who are classified as ignorant of the existence of rules regarding regulations that prohibit people from carrying firearms or sharp weapons in public places. Suggestions for the community, especially parents, to supervise and guide their children to be careful in socializing and educating about what matters are their duties and responsibilities as students, so as not to violate the law. Moreover, to the extent of causing harm to himself and others.